Influence of branche harvest period in rooting of coffee stem cuttings (Coffea arabica L. cv "Mundo Novo") (Scientia Agricola, 1992)
Timing of stem cuttings has large influence on rooting and on vegetative propagation of coffee seedlings. Auxin treatments on cuttings also promote root formation. The present research evaluated auxins and boron actions and the influence time of coffee-tree branch havest time, over rooting of orthotropous semi-hardwood branches of coffee (Coffea arabica L. cv . Mundo Novo) stem cuttings. The trial was performed monthly, observing the cuttings 90 days after planting: number of rooted cuttings and total root number. It was concluded that the best branch harvesting time is in the rainy season, whem cuttings show satisfatory results. Treatments with NAA 200 ppm plus boric acid, promoted higher rooting percentage.